Money demand in Mexico: a nonlinear ARDL approach - Durmaz, Nazif; Jie, Tairu (Economics and Business Letters, 2024)
This paper examines the relationship between Mexican money demand and three economic factors: real income, inflation rate and exchange rate, and the relationship between exchange rate and money demand is the most concerned. Using the quarterly data of Mexico from 2000 to 2022, we explore whether the exchange rate will symmetrically affect the demand for money in the short and long term. The results show that in the long run, the impact of real income and inflation rate on money demand is the same as the conjecture, both are positive. However, the present paper does not find an asymmetric effect of the exchange rate, possibly due to the lack of research data or the short time span.